Business Strategy Development and Planning - Ariyanti, Dian Ayu; Afrianti , Athika Dewi; Yarangga , Mitha Monik; Andarini, Sonja; Kusumasari, Indah Respati (PT FORMOSA CENDEKIA GLOBAL, 2024)
Every business needs a plan, especially today when funding and competition are so tight and increasingly advanced. From large companies to new businesses, doing business in Indonesia is becoming increasingly complex, with many competitors selling the same products and services. To reduce possible risks, it is best for companies to have a business plan before starting their business. The more competitors there are, the greater the possibility that consumers will be persuaded to buy the product or service being sold. Many business people only chase big profits without planning or thinking about the risks that might arise. Business planning that can be carried out consists of initial investment, initial funding requirements plan, estimated average sales, equipment purchases, cost of goods sold, income analysis, cash flow analysis, net present value (NPV), payback period, legal aspects, and methods. Data collection Business development planning is also an important step to ensure business success.